Advances in The Human Side of Service Engineering Proceedings of the AHFE 2017 International Conference on The Human Side of Service Engineering, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Freund, Louis E.; Cellary, Wojciech (Advances in Intelligent Systems and Computing,, 2018)
This book explores the different ways in which human-factors engineering influences organizations' and enterprises' well-being and competitiveness. It covers a wealth of interrelated topics such as service engineering, service science, human-computer interaction, service usability, attitude and opinion assessment, servicescape design and evaluation, and training for service delivery. Further topics include service systems modeling, anthropology in service science, and customer experience, as well as ethical issues and the impact of an aging society. Based on the AHFE 2017 International Conference on The Human Side of Service Engineering, held on July 17-21, 2017, in Los Angeles, California, USA, the book provides readers with a comprehensive, general view of current research and challenges in the important field of service engineering. It also provides practical insights into the development of services for different kinds of organizations, including health care organizations,aviation providers, manpower allocation, hospitality and entertainment, as well as banking and financial institutions.